IMPLEMENTING TASK-BASED LANGUAGE TEACHING: A SOLUTION FOR ENGLISH TEACHERS TO IMPROVE STUDENTS’ SPEAKING SKILL - Dewi Nopita (Universitas Sebelas Maret, 2017)
Teaching speaking brings a different challenge for teachers who teach English as a foreign language. Most English Foreign Language students are reluctant to speak. When the students speak, they focus more on grammar, not on meaning. To cope with this problem, English teachers can implement Task-Based Language Teaching (TBLT). TBLT is an approach which is based on the assumption that accuracy is acquired after fluency or after successful communication. This approach provides an environment which best promotes the natural language learning. Throughout this article, I would like to describe how TBLT work in each stage of teaching speaking as a foreign language.